DESAIN APLIKASI PENCOCOKAN STRING PADA KAMUS ISTILAH SEL (BIOLOGI) MENGGUNAKAN METODE BOYER MOORE - TRIASE TRIASE (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2017)
Science is an important part of man because it plays a major role in changing the mindset of man. Education is a human medium for gaining knowledge. The world of education, especially biology is a science that studies the knowledge of living things in the universe consists of humans, plants and animals, they have a cell with a unique name and very difficult to remember. Dictionaries are books containing terms, meanings and words used as a tool to translate the language. The dictionary is usually physically always thick so that when taken will be heavy and takes place. Bioinformatics is defined as the application of computational tools and analysis to capture and interpret biological data. The design of a cell term dictionary application so that it is easily searched for its cell term is part of the result of bioinformatics, and to generate a computerized search term that is difficult to use Boyer Moore algorithm. The Boyer Moore algorithm is the best string matching algorithm due to its ability to quickly match the searched strings. Application of Bayor Moore algorithm in dictionary application required design of process model using DFD and design database can be easily implemented to application system